(untitled) (Perner’s Contacts, 2009)
Defined (limited) maintenance resources are available while maintenance planning of rail vehicles. Often the limitation affects determinate time for maintenance and maintenance costs value. Incorrect setting of both parameters while maintenance planning results in non-completion of maintenance objectives. The interrelationship of both limitative quantities is described by the stochastic maintenance model, which enables to determine the probability of maintenance objective completion.